MOBILIZING FUNDS BY INTERRELATING CHARITABLE DONATIONS THROUGH WAQF OF HIGHER EDUCATION - Nazmul Hoqu, Muhammad (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
In the light of the blessed attributes of waqf as perpetual charity this paper intends to study the organization and ethico-economic yields from the waqf of Higher Education project. The paper will establish the values of sustainability and yields that permeate in society at large without diminish when the charity of waqf is well organized. The paper thereby develops a system model of participatory interrelationship for the objective of attaining social wellbeing for the common good. Sustainability is defined in terms of moral, ethical, and social values that are generated across intertemporal continuum of knowledge, space, and time. Such values are endogenously integrated with socioeconomic yields of the economic and financial type. The institution of Higher Education is shown to be established by the waqf dynamics of inter-causal circular relations between the variables of the wellbeing criterion. A modelled approach and its simple empirical valuation are formalized.